2007
DOI: 10.1007/s00049-007-0368-x
|View full text |Cite
|
Sign up to set email alerts
|

Ceroplastes albolineatus, the first scale insect shown to sequester pyrrolizidine alkaloids from its host-plant Pittocaulon praecox

Abstract: The occurrence of pyrrolizidine alkaloids (PAs) in Pittocaulon (ex Senecio) praecox (Asteraceae) a species endemic to Mexico was established. The aboveground plant organs contain the 1,2-saturated monoester 7-angeloyl-dihydroxyheliotridane together with a small proportion of its 9-angeloyl isomer as major alkaloid. The monoesters are accompanied by the macrocyclic otonecine derivative senkirkine. Roots contain only related macrocyclic PAs with senecionine, senkirkine and platyphylline as major components; mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Ceroplastes albolineatus (Coccidae) sequesters senkirkine and other PAs from Pittocaulon praecox (Asteraceae) and stores them as tertiary alkaloids (Loaiza et al 2007). The aphid Aphis jacobaeae (Aphididae) accumulates PAs from the phloem of Senecio spp.…”
Section: Pyrrolizidine Alkaloids In Sternorrhynchamentioning
confidence: 99%
“…Ceroplastes albolineatus (Coccidae) sequesters senkirkine and other PAs from Pittocaulon praecox (Asteraceae) and stores them as tertiary alkaloids (Loaiza et al 2007). The aphid Aphis jacobaeae (Aphididae) accumulates PAs from the phloem of Senecio spp.…”
Section: Pyrrolizidine Alkaloids In Sternorrhynchamentioning
confidence: 99%
“…In addition, the roots afforded 73d and the mixtures: 73a-c, 74a-c, 67a-d, and 75a-f. In 2007, Céspedes et al reported the GC-MS analysis of P. praecox [38]. This analysis permitted to establish the presence of the PAs senecionine (8), integerrimine (12a), platyphylline (39), senkirkine (58), neosenkirkine (76), neoplatyphylline (77), 9-angeloyldihydroxyheliotridane (78a), and 7-angeloyldihydroxyheliotridane (78b) in the plant.…”
Section: Genus Pittocaulonmentioning
confidence: 99%
“…Sequestration of PAs from plants by the immature and/or the adult stage is known for the grasshopper Zonocerus variegatus (Pyrgomorphidae) (Bernays et al 1977;Biller et al 1994), the aphid Aphis jacobaeae and the coccid Ceroplastes albolineatus (Witte et al 1990;Loaiza et al 2007), the true bugs Neacoryphus bicrucis (Lygaeidae), Largus rufipennis (Largidae) and Lopidea instabile (Miridae) (McLain 1984;McLain and Shure 1985;Klitzke and Trigo 2000), many arctiid moths and all danaine and ithomiine butterflies (for reviews see: Boppré 1986Boppré , 1990Brown and Trigo 1995;Hartmann and Witte 1995;Weller et al 1999;Trigo 2000Trigo , 2008Nishida 2002;Conner and Weller 2004;Opitz and Müller 2009), the leaf beetles belonging to the genera Longitarsus, Oreina and Platyphora (for reviews see: Pasteels and Hartmann 2004;Opitz and Müller 2009), and the beetle Chauliognathus fallax (Cantharidae) (Klitzke and Trigo 2000). Other insect species were described to visit PA-sources (see below), but whether they sequester PAs or not remains to be investigated.…”
Section: Hägele and Rowell-rahier (2000)mentioning
confidence: 99%